Cobalt phosphide supported by two-dimensional molybdenum carbide (MXene) for the hydrogen evolution reaction, oxygen evolution reaction, and overall water splitting. Issue 37 (6th September 2021) - Liu, Shilong; Lin, Zongshan; Wan, Rendian; Liu, Yonggang; Liu, Zhe; Zhang, Shuidong; Zhang, Xiaofeng; Tang, Zhenghua; Lu, Xiaoxing; Tian, Yong
Abstract : CoP/Mo2 CT x is prepared as efficient catalyst for HER, OER, and water splitting. DFT calculations revealed that it has optimal H* adsorption free energy and MXene plays a critical role to boost HER, while CoP is transformed into Co–OOH in OER. Abstract : Developing a low cost, high performance, and durable bifunctional catalyst to boost the hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) for water splitting is a critical yet challenging task. Transition metal phosphides have been identified as promising dual functional catalysts recently. Herein, we report a facile strategy to construct a heterostructure catalyst by integrating cobalt phosphide with molybdenum carbide (MXene). The CoP/Mo2 CT x (T is the surface terminal group) catalyst exhibited good HER activity with an overpotential of 78 mV at a current density of 10 mA cm −2, close to that of the Pt/C benchmark, and its OER performance is markedly better than that of the RuO2 benchmark, evidenced by a very small overpotential of 260 mV at 10 mA cm −2 in 1 M KOH. Impressively, when employed for overall water splitting, CoP/Mo2 CT x also outperformed the Pt/C + RuO2 combination with a voltage of 1.56 V @ 10 mA cm −2 . Density functional theory (DFT) calculations revealed that CoP/Mo2 CT x has appropriate water adsorption especially the optimal H* adsorption free energy (Δ G H* ), and the Mo2 C MXene support can significantly increase the total density of states and downshift the d-band center for the HER, while for the OER, multiple characterization techniques of CoP/Mo2 CT x post the OER test show that CoP in the catalyst can be transformed into Co–OOH during the electrocatalytic process. This study can provide a pathway for the design and fabrication of MXene-supported noble-metal-free bifunctional catalysts toward practical water splitting and energy conversion.